RISK ANALYSIS IN SANDWICH PANEL PRODUCTION WITH THE INTEGRATION OF FMEA AND FTA METHODS - Qur'ani , Nur Azmil; Wahyuni, Hana Catur (Journal for Technology and Science, 2024)
General Background: Ensuring consistent product quality is crucial for maintaining competitive advantage, especially in manufacturing. PT. Starr Panel Industry, a company in the refrigeration sector, focuses on high-quality sandwich panels but experiences frequent defects in its production processes. Specific Background: Despite prioritizing premium raw materials, the company faces recurring product failures, particularly in the finishing phase, which affect production flow and on-time delivery. Knowledge Gap: Current quality assurance measures at PT. Starr Panel Industry lack a systematic approach to identifying and prioritizing the root causes of defects, hindering the development of targeted improvement strategies. Aims: This study aims to identify, analyze, and address potential failure modes and their root causes within the production processes, employing Failure Modes and Effects Analysis (FMEA) and Fault Tree Analysis (FTA). Results: The findings reveal that the finishing process has the highest Risk Priority Number (RPN) of 112, primarily due to insufficient adherence to standard operating procedures (SOPs) by the workforce. Novelty: The integration of FMEA and FTA provides a comprehensive failure analysis model, with FMEA ranking failure risks and FTA tracing them to foundational causes, offering a new dual-method approach to improve operational standards effectively. Implications: Implementing the proposed FMEA-FTA framework can significantly reduce product defects, improve quality consistency, and minimize delivery disruptions, especially in the critical finishing stage. Emphasizing SOP compliance across divisions, particularly in finishing, can lead to sustained quality improvements and enhanced operational efficiency in sandwich panel production.